Pomeron physics and QCD - Nachtmann, Otto (Arxiv, 2003)
We review some theoretical ideas concerning diffractive processes. We discuss the Regge Ansatz for the pomeron and the two pomeron model. Then we present the results obtained from nonperturbative QCD for high energy scattering. There we can extract from elastic scattering data the parameters describing the QCD vacuum, in particular the string tension.